Men in black - Sonnenfeld, Barry; Parkes, Walter F.; McDonald, Laurie; Solomon, Ed.; Jones, Tommy Lee, 1946-; Smith, Will, 1968-; Fiorentino, Linda; D'Onofrio, Vincent; Torn, Rip, 1931-; Shalhoub, Tony, 1953-; Cunningham, Lowell; Columbia Pictures; et al. (Culver City, Calif. : Columbia TriStar Home Video, 2002)
New York City is being threatened by a villainous bug who has inhabited the body of a farmer. The mission is to locate and exterminate the bug before it destroys the planet.
Based on the Marvel comic by Lowell Cunningham.
Originally produced as motion picture in 1997.
Special features: Disc 1, digitally mastered audio and anamorphic voice ; widescreen and full screen presentations ; visual and audio commentary ; subtitles in English, French, Spanish, Cantonese, Mandarin ; Disc 2, MIM II teaser trailer ; secret files - sneak peek at MIB II ; extended and alternate scenes ; music video by Will Smith and Mikey ; storyboard comparisons; theatrical trailers ; MEN IN BLACK documentary ; animated menues ; production notes ; scene editing workshop ; conceptual art gallery ; DVD ROM and web links.
Director of photography, Don Peterman ; film editor, Jim Miller ; music, Danny Elfman.
Tommy Lee Jones, Will Smith, Linda Fiorentino, Vincent D'Onofrio, Rip Torn, Tony Shalhoub.
Rated PG-13.
Keywords: Men in black (UFO phenomenon); Life on other planets -- Drama; Science fiction films; Feature films; Video recordings for the hearing impaired; Extraterrestrial beings -- Drama; Documentary films